Complementary description of three species of Steneotarsonemus (Acari: Tarsonemidae) from rice agroecosystems of Eastern India with notes on their taxonomic status, spatial distribution, intraspecific variation and species composition - Ganguly, Moumi; Mondal, Priyankar; Karmakar, Krishna (Zootaxa, 2022)
Rice agroecosystems are inhabited by a number of Steneotarsonemus species worldwide with various host plant relationships and taxonomic identities. To clarify this situation, a large-scale survey was initiated in rice growing belts of eastern India and this revealed the presence of four species of Steneotarsonemus viz. S. furcatus, S. konoi, S. spinki and S. subfurcatus. However, only S. spinki and S. subfurcatus were found infesting rice while the other species were found associated with a number of graminaceous weeds. We found three intraspecific variants within the population of S. spinki which are differentially distributed in nine separate locations covering four states across eastern India. A new subgenus Linzhangia is proposed for inclusion of exceptionally unique S. subfurcatus possessing setaceous v2 on prodorsum of female. Additionally, the population of S. spinki and S. subfurcatus were found to be differentially distributed across five different agroclimatic zones of West Bengal with S. spinki being the dominant species.